Ecological and morphological variation of darters among assemblages in Oklahoma streams - Hopper, Garrett W. (Kansas State University, 2015)
Environmental variation can shape phenotypic variation in organisms. Most evidence for trait differentiation along environmental gradients comes from analyses of dichotomous habitat types that differ in only one or few environmental factors. In reality, however, environmental variation is often more subtle, gradual, and multifarious. I investigated geographic variation in body shape, trophic resource use, and individual diet specialization in two species of darters (Etheostoma spectabile and E. flabellare; Percidae) that occur along river gradients. I explicitly tested how abiotic and biotic environmental factors shape trait variation within and between species. Results indicated significant among population variation in the body shape of both species. Population differences in body shape were correlated with variation in substrate composition. Although body shape analyses revealed a small but significant signal of convergent evolution of body shape when both species occur in sympatry, E. spectabile and E. flabellare mostly exhibited unique responses to shared sources of selection. The analyses of darter trophic resource use uncovered significant resource partitioning between the two species and geographic variation in diets that is likely driven by differences in resource availability. Furthermore, the majority of populations exhibited significant individual specialization. Variation in individual specialization in populations of E. flabellare was related to invertebrate density and competitor richness, and in E. spectabile to the combined effects of invertebrate density and invertebrate diversity. My results indicate substantial variation in trophic resource use among individuals, populations, and species of small-bodied fishes that are typically assumed to be generalist insectivores. Variation in diet specialization may be more widespread than previously considered, and ecological opportunity is an important factor in shaping trophic resource use of individuals and populations. Overall, the results indicate that even subtle and gradual environmental variation can induce substantial variation in phenotypes on a relatively small spatial scale.
Keywords: Ecological gradients; Darters; Local adaptation; Geometric morphometrics; Diet variation; Individual specialization; Biology (0306); Ecology (0329)